Performance of an ultrasound diagnostic algorithm for acute dyspneic patients in the emergency department: an EMERALD-US protocol - Adrien Bassand; Tahar Chouihed; Nicolas Girerd; Xavier Lepage; Ludovic Merckle; Anthony Chauvin; Aurélien Buessler; Deborah Jaeger; Kevin Duarte; Charlene Duchanois; Jérôme Bokobza; Alice Penine; et al. (BMJ Open)
Introduction Dyspnoea frequently leads to admissions in the Emergency Department (ED). Rapid and accurate diagnosis, specifically to distinguish acute heart failure from pneumonia and exacerbations of chronic obstructive pulmonary disease (COPD), is imperative to initiate appropriate therapy. This study aims to evaluate the feasibility and performance of the EMERgency ALgorithm efficiency for Dyspneic patient-UltraSound (EMERALD-US) algorithm using ultrasound (US) to diagnose the etiology of dyspnea in the ED-admitted patients.Method and analysis 225 patients of 50 years and above, presenting with acute non-traumatic dyspnoea, across six participating EDs will be enrolled. Patients will undergo a lung, a simplified four-chamber cardiac and a venous US. A physician, blinded to any clinical data or previous results, will execute the algorithm. The algorithm’s performance will be assessed using a receiver operating characteristic (ROC) curve. Secondary objectives include an evaluation of the protocol’s feasibility in the ED, an assessment of the concordance between the EMERALD-US algorithm diagnoses and results from other diagnostic tests (including laboratory work and imaging), as well as an evaluation of the algorithm’s performance in diagnosing other causes of dyspnoea, such as pulmonary embolism or pleural effusion, and the 30-day mortality rate.Ethics and dissemination The study protocol was approved by the French Committee for the Protection of Persons (CPP) (RCB n°2018-A02136-49). Misdiagnosis of dyspneic patients on ED admission has been associated with inappropriate treatment, prolonged hospital stays and increased mortality, particularly among elderly patients. The implementation of protocols like the EMERALD-US algorithm can help physicians in expedited decision-making and diagnosis without increasing ED visit durations.Trial registration number NCT03691857.